Institutional development for flood disaster management rural development in Bangladesh: a case study of Kanchanpur union - Mohit, Mohammad Abdul; Mustafa, Golam (Centre for Development Research Bangladesh, 1995)
Institutional development for flood disaster management should emphasize on the reduction of socio-economic and infrstructural vulnerabilities. Institutional/ infrastructural vulnerabilities are dependent on changes in structural, legal, financial/ technical, managerial and motivational aspects of those institutions.